The Coupling Coordination Evaluation of Sustainable Development between Urbanization, Housing Prices, and Affordable Housing in China - Lida Wang; Xian Rong; Lingling Mu (Discrete Dynamics in Nature and Society)
For the past few years, China’s urbanization process has been in a state of rapid and variable development. With many migrants flowing from rural to urban area, the change in the urban structure and the trend of the economic development has led to a rapid development of the real estate market. However, the conflict between the migrants and the local low- and middle-income groups in respect of demand for basic housing has become a concern. Based on Chinese time-series data from 2008 to 2018, this study establishes an evaluation indicator system to consider the influence of urbanization, housing prices, and affordable housing and analyzes the comprehensive development level and coordination relationship using the methods of range standardization, entropy weight model, and coupling coordination. The results show that the comprehensive development levels of housing prices and affordable housing are both in a state of fluctuating growth. From 2008 to 2018, the coupling degree between urbanization, housing prices, and affordable housing was high, while the coupling coordination degree between the three subsystems increased from reluctant coordination to satisfactory coordination; this clearly shows that the relationships between urbanization, housing prices, and affordable housing are mutually coupled and promoted. Furthermore, based on the coupling coordination relationships between the three subsystems, this study discusses the sustainable development of urbanization and provides some suggestions for regional government. The conclusions have practical significance for China and other developing countries to coordinate housing prices and affordable housing in the process of rapid urbanization.